A Phase Ib Study of Axitinib in Combination with Crizotinib in Patients with Metastatic Renal Cell Cancer or Other Advanced Solid Tumors. (6th June 2019) - Michaelson, M. Dror; Gupta, Shilpa; Agarwal, Neeraj; Szmulewitz, Russell; Powles, Thomas; Pili, Roberto; Bruce, Justine Yang; Vaishampayan, Ulka; Larkin, James; Rosbrook, Brad; Wang, Erjian; Murphy, Danielle; et al.
Abstract: Lessons Learned: The combination of axitinib and crizotinib has a manageable safety and tolerability profile, consistent with the profiles of the individual agents when administered as monotherapy. The antitumor activity reported here for the combination axitinib/crizotinib does not support further study of this combination treatment in metastatic renal cell carcinoma given the current treatment landscape. Background: Vascular endothelial growth factor (VEGF) inhibitors have been successfully used to treat metastatic renal cell carcinoma (mRCC); however, resistance eventually develops in most cases. Tyrosine protein kinase Met (MET) expression increases following VEGF inhibition, and inhibition of both has shown additive effects in controlling tumor growth and metastasis. We therefore conducted a study of axitinib plus crizotinib in advanced solid tumors and mRCC. Methods: This phase Ib study included a dose‐escalation phase (starting doses: axitinib 3 mg plus crizotinib 200 mg) to estimate maximum tolerated dose (MTD) in patients with solid tumors and a dose‐expansion phase to examine preliminary efficacy in treatment‐naïve patients with mRCC. Safety, pharmacokinetics, and biomarkers were also assessed. Results: No patients in the dose‐escalation phase ( n = 22) experienced dose‐limiting toxicity; MTD was estimated to be axitinib 5 mg plus crizotinib 250 mg. The most common grade ≥3 adverse events were hypertension (18.2%) and fatigue (9.1%). In the dose‐expansion phase, overall response rate was 30% (95% confidence interval [CI], 11.9–54.3), and progression‐free survival was 5.6 months (95% CI, 3.5–not reached). Conclusion: The combination of axitinib plus crizotinib, at estimated MTD, had a manageable safety profile and showed evidence of modest antitumor activity in mRCC.